2020
DOI: 10.4012/dmj.2019-208
|View full text |Cite
|
Sign up to set email alerts
|

The orthodontic bonding properties of human enamel after cryopreservation

Abstract: The aim was to investigate the effect of cryopreservation on the enamel bonding properties of orthodontic brackets. Sixty-six human premolars were randomly allocated to a control group or a cryopreserved group. Conventional stainless-steel orthodontic brackets were bonded with a light cure adhesive on the buccal side of the premolars. The shear bond strength (SBS) was determined at a crosshead speed of 1 mm/min. The SBS and adhesive remnant index (ARI) were evaluated respectively by an independent samples t te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated that cryopreservation does not affect dentin permeability [4], dentin bond strength [5] or enamel bond strength [6]. Although the Vickers test demonstrated that the hardness of enamel was not affected by cryopreservation, a longitudinal fracture was found in 1 4 of the teeth after freezing [7].…”
Section: Introductionmentioning
confidence: 93%
“…Previous research has demonstrated that cryopreservation does not affect dentin permeability [4], dentin bond strength [5] or enamel bond strength [6]. Although the Vickers test demonstrated that the hardness of enamel was not affected by cryopreservation, a longitudinal fracture was found in 1 4 of the teeth after freezing [7].…”
Section: Introductionmentioning
confidence: 93%